Cardiomyocyte-Specific Deletion of the Vitamin D Receptor Gene Results in Cardiac Hypertrophy - Chen, Songcang; Law, Christopher S.; Grigsby, Christopher L.; Olsen, Keith; Hong, Ting-Ting; Zhang, Yan; Yeghiazarians, Yerem; Gardner, David G. (Circulation (New York, N.Y.), 2011)
A variety of studies carried out using either human subjects or laboratory animals suggest that vitamin D and its analogues possess important beneficial activity in the cardiovascular system. Using Cre-Lox technology we have selectively deleted the vitamin D receptor (VDR) gene in the cardiac myocyte in an effort to better understand the role of vitamin D in regulating myocyte structure and function. Targeted deletion of the exon 4 coding sequence in the VDR gene resulted in an increase in myocyte size and left ventricular weight/body weight versus controls both at baseline and following a 7-day infusion of isoproterenol. There was no increase in interstitial fibrosis. These knockout mice demonstrated a reduction in end-diastolic and end-systolic volume by echocardiography, activation of the fetal gene program (ie, increased atrial natriuretic peptide and alpha skeletal actin gene expression), and increased expression of modulatory calcineurin inhibitory protein 1 (MCIP1), a direct downstream target of calcineurin/nuclear factor of activated T cell signaling. Treatment of neonatal cardiomyocytes with 1,25-dihydroxyvitamin D partially reduced isoproterenol-induced MCIP1 mRNA and protein levels and MCIP1 gene promoter activity. Collectively, these studies demonstrate that the vitamin D-VDR signaling system possesses direct, antihypertrophic activity in the heart. This appears to involve, at least in part, suppression of the prohypertrophic calcineurin/NFAT/MCIP1 pathway. These studies identify a potential mechanism to account for the reported beneficial effects of vitamin D in the cardiovascular system.